Peace Project as an Effort to Support Peace Awareness and Tolerance between Religious Communities in Jakarta, Indonesia - Faliqul Jannah Firdausi; Muhammad Mahmudi; Andi Muhammad Arief Malleleang (At-Tafkir, 2024)
This research investigates the response of Muslim youth to the Peace Project, an Indonesian Global Peace Foundation (GPF) initiative aimed at increasing peace and tolerance among religious believers. This research uses qualitative research methods with a case study design. The focus of this study was a visit to the Zion Church and Candra Prabha Temple, thirty Muslim participants with data collection in the form of observations and surveys. Research findings show: 1) The Peace Project succeeded in facilitating contact between religious youth groups; 2) Muslim participants showed enthusiasm for the activity, suggesting a longer duration and visits to other places of worship; and 3) the need for academic speakers to guide discussions about respecting diverse religions. This research offers recommendations for improving interfaith initiatives, better planning activities, contributing to knowledge of religious tolerance, and increasing public awareness about interfaith engagement for a more tolerant society, based on positive responses among Jakarta's Muslim youth.